2012
DOI: 10.1002/cbic.201200499
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylarginine‐Dimethylaminohydrolase‐2 (DDAH‐2) Does Not Metabolize Methylarginines

Abstract: Free endogenous methylarginines, N(ω)-monomethyl-L-arginine (L-NMMA) and N(ω),N(ω')-dimethyl-L-arginine (ADMA), inhibit NO synthases (NOSs) and are metabolized by dimethylargininedimethylaminohydrolase (DDAH). A postulated metabolism has been shown several times for DDAH-1, but the involvement of DDAH-2 in the degradation of ADMA and L-NMMA is still a matter of debate. Determination of the isoform-specific DDAH protein expression profiles in various porcine tissue types shows a correlation of DDAH activity onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…For example, in addition to the brain, DDAH1 is known to express in the pancreas, skeletal muscle, heart, liver, and kidneys. Recent genetic [ 10 ] and biochemical [ 11 ] studies report that DDAH1 is mainly responsible for the enzymatic breakdown of ADMA into citrulline and methylamine. The clearance of ADMA by DDAH is however compromised by several cardiovascular risk factors that impair the expression and/or activity of DDAH [ 8 ].…”
Section: Nitric Oxide Synthesis Function and Endogenous Regulatimentioning
confidence: 99%
“…For example, in addition to the brain, DDAH1 is known to express in the pancreas, skeletal muscle, heart, liver, and kidneys. Recent genetic [ 10 ] and biochemical [ 11 ] studies report that DDAH1 is mainly responsible for the enzymatic breakdown of ADMA into citrulline and methylamine. The clearance of ADMA by DDAH is however compromised by several cardiovascular risk factors that impair the expression and/or activity of DDAH [ 8 ].…”
Section: Nitric Oxide Synthesis Function and Endogenous Regulatimentioning
confidence: 99%
“…The isoform 1 of the enzyme dimethylarginine dimethylaminohydrolase (DDAH1) plays a critical role in the metabolism of the endogenous methylated arginines, asymmetric N G ,N G -dimethyl-L-arginine (ADMA) and N G -monomethyl-L-arginine (NMMA), into L-citrulline and dimethylamine [ 1 , 2 , 3 ]. As both ADMA and NMMA are potent endogenous inhibitors of the three isoforms of nitric oxide (NO) synthase (NOS), DDAH1 regulation significantly influences NO synthesis [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…DDAH-2 appears prevalent in pancreatic islet cells [5] and infected tissues [6]. In addition, Altman et al reported a study showing high expression of DDAH-2 in porcine immune tissues [7]. The two isoforms are both expressed in kidney [8,9,10], heart [11,12], adipose tissue [13], placenta and trophoblasts [14], and the liver [15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%